Corporate governance and audit fees: Evidence from a developing country - Muhammad Umar Farooq; Irfan Kazim; Muhammad Usman; Ijaz Latif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
In this paper, we investigate the effect of board and audit committee quality on the audit fees in the context of developing country of Pakistan. We us five years data of KSE-100 index companies listed on Pakistan Stock Exchange. To draw the inference, we use the Partial Least Square based Structural Equation Modeling. We find that effective board quality (measured through board size, board independence, CEO duality, chairperson independence, board equity holding, and board diligence) is positively associated with external auditor fees. This finding suggests that, high quality board demands higher quality audit to have further assurance on the quality of financial reporting. While, we find audit committee effectiveness (measured through audit committee size, audit committee independence, and audit committee diligence) reduces the external audit fee, which supports our notion that, the high quality audit committee will ensure reliable financial reporting which reduces external auditor's efforts that result in lower audit fees.
Keywords: 330; board quality; audit fees; audit committee effectiveness; partial least square